The Bogor Regency Regional People's Representative Council's Legislative Function in the Preparation of Regional Regulations - M Syaiful Azhar; Mufidah Mufidah (UIN JAKARTA, 2021)
The legislative function of the DPRD has not run smoothly, in some areas it is still experiencing various difficulties. Many Local Regulation Draft Initiatives (Raperda) come from the Regional Government as an executive agency. Meanwhile, the institution that enforces the aspirations of the community, the DPRD provides a lot of participation in the determination of the Perda. The purpose of the research is to study the implementation of the legislative function of the DPRD in Bogor City in 2013-2018. This research uses a qualitative method with literature approach. Data sources used in this study consisted of primary, secondary and tertiary legal materials, policy considerations of the political elite in this case the Bogor City Council, books, journal of legal. The results of the research are the legislative function carried out by the Bogor City DPRD in accordance with Law Number 23 of 2014 concerning Regional Government, which wrongly performs the legislative function that can capture the aspirations of the people in Bogor City, by receiving reports or complaints from the people of Bogor City the problem of dissatisfaction of a service. Although in its implementation is still not optimal because there are still obstacles in legislation.